Influence of anxiety and alexithymia on brain activations associated with the perception of others' pain in autism. (4th May 2019) - Lassalle, Amandine; Zürcher, Nicole R.; Porro, Carlo A.; Benuzzi, Francesca; Hippolyte, Loyse; Lemonnier, Eric; Åsberg Johnels, Jakob; Hadjikhani, Nouchine
ABSTRACT: The circumstances under which empathy is altered in ASD remain unclear, as previous studies did not systematically find differences in brain activation between ASD and controls in empathy-eliciting paradigms, and did not always monitor whether differences were primarily due to ASD "per se", or to conditions overlapping with ASD, such as alexithymia and anxiety. Here, we collected fMRI data from 47 participants (22 ASD) viewing pictures depicting hands and feet of unknown others in painful, disgusting, or neutral situations. We computed brain activity for painful and disgusting stimuli (vs. neutral) in whole brain and in regions of interest among the brain areas typically activated during the perception of nociceptive stimuli. Group differences in brain activation disappeared when either alexithymia or anxiety – both elevated in the ASD group – were controlled for. Regression analyses indicated that the influence of symptoms was mainly shared between autistic symptomatology, alexithymia and anxiety or driven by unique contributions from alexithymia or anxiety. Our results suggest that affective empathy may be affected in ASD, but that this association is complex. The respective contribution of alexithymia and anxiety to decreased affective empathy of people with ASD may be due to the association of those psychiatric conditions with reduced motor resonance/Theory of Mind.